Спостереження та лікування тяжкого занедбаного первинного гіперпаратиреозу з аналізом недоліків тривалого діагностично-лікувального процесу - Шептуха, С. А.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
Common reasons of delayed diagnosis and treatment faults in patients with primary hyperparathyroidism (PHPT) are discussed in the article on the example of advanced case of parathyroid carcinoma. Among them authors called insufficient awareness of non-endocrinologist about PHPT, polymorphism of PHPT clinical signs, lack of experience of parathyroid surgery in general hospitals, absence of screening of serum calcium. Even in case of advanced bone destructions and renal stones symptoms laboratory confirmation of severe PHPT diagnosis was extremely delayed.